Internalization, Habituation, and Reflection of Islamic Values through Nusantara Local Traditions: Constructing a Character Education Model in Madrasah - Agung Syarifudin; Anna Setiani; Siti Khoirotun Nafi’ah; Samiyono (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Character education in Indonesian Islamic primary schools (madrasah) remains predominantly textual and normative, limiting its effectiveness in cultivating deep moral habituation and critical reflection. This study constructs an empirically grounded character education model integrating three sequential yet cyclical stages internalization, habituation, and reflection of Islamic values, using Nusantara local traditions as the central pedagogical medium. A qualitative multiple case study design was employed across two purposively selected madrasah ibtidaiyah in Central Java and East Java, Indonesia. Data were generated through in-depth semi-structured interviews with principals, Islamic Religious Education (IRE) teachers, and parents; participant observation of classroom and extra-curricular activities; and curriculum document analysis. Thematic analysis following the Miles Huberman interactive model was applied. Findings reveal three interlocking mechanisms: (1) internalization through cultural contextualization, whereby Islamic values such as taʿawun (mutual cooperation), shuʺra (consultation), and adab (Islamic etiquette) are taught via corresponding local practices of gotong royong, musyawarah, and Javanese tata krama; (2) habituation through structured engagement in barzanji recitation, kenduri communal feasts, and daily greeting rituals aligned with Islamic law; and (3) reflection through guided journaling and Socratic dialogue that transforms routine practice into permanent moral consciousness. The resulting IHR (Internalization Habituation Reflection) model is cyclical, locally grounded, and critically oriented, offering a theoretically coherent and practically replicable alternative to prevailing textual-normative character education approaches in Indonesian madrasah and comparable Islamic educational contexts globally.